Public Interest Law in Criminal Code Article 310(3) as the Basis to Eliminate Crime in Journalism - Fredy Christian Sipayung, Ronald; Danil, Elwi; Mulyadi, Mahmud; Yunara, Edi (KnE Social Sciences, 2024)
In the Republic of Indonesia, legal norms and rules prioritize the public interest over state, group, and individual interests. Article 310 paragraph (3) of the Criminal Code allows for the removal of offenses committed in the public interest. However, using the public interest as a justification for press activities can lead to controversy due to unreliable or false news sources. Law No. 40 of 1999 concerning the Press, and the Press Council, an independent regulatory body established in 1966, protect press freedom and regulate the press according to the Journalistic Code of Ethics. However, due to perceived inadequacies, press violations are often resolved through press releases rather than relying on the Code as a legal basis. A normative legal research method was used to analyze the relationship between the Criminal Code and the Press Law, revealing that press freedom is a fundamental human right protected by the Constitution. The Press Law functions as a Lex specialis of the Criminal Code, addressing issues such as defamation, insults, and ridicule, and resolving disputes within the press while prioritizing the public interest over government interests. Keywords: Public Interest, Freedom of the Press